Molecular systematics and biodiversity of the Cryptotis mexicanus group (Eulipotyphla: Soricidae): two new species from Honduras supported. Issue 2 (17th February 2018) - Baird, Amy B.; McCarthy, Timothy J.; Trujillo, Robert G.; Kang, Yuan Yuan; Esmaeiliyan, Mehdi; Valdez, Joselyn; Woodman, Neal; Bickham, John W.
Abstract : Small-eared shrews of the genus Cryptotis (Mammalia: Eulipotyphla: Soricidae) are widespread in the northern Neotropics. Systematic studies of these shrews over the past two decades have revealed previously undocumented morphological and species diversity, resulting in a quadrupling of the number of recognized species. Unfortunately, a small proportion of the species in the genus have been included in molecular phylogenetic studies, and evolutionary relationships within the genus are incompletely known. Traditionally, species have been assigned to four or five morphologically defined 'species groups', but tests of the monophyly of some of these groups show weak support and relationships amongst species groups remain somewhat speculative. The largest species group is the C. mexicanus group inhabiting Mexico and northern Central America. We studied sequences from mitochondrial cytochrome-b and 16S genes, as well as nuclear ApoB and BRCA1 genes from 22 species of Cryptotis, including 15 species in the C. mexicanus group. Our combined analysis shows that the C. goldmani subgroup is very weakly supported as monophyletic; however, the C. mexicanus group as a whole is not monophyletic. Our molecular phylogenetic analyses confirm the distinctiveness of two newly described species ( C. celaque and C. mccarthyi ) from isolated highlands of western Honduras and illustrate their relationship with other species formerly considered part of a widespread C. goodwini .